The Extremal and Infra-Topological Spaces over a Finite Set-A Computational Approach with Maple. - G. El Turki, Taha (Libyan Journal of Science &Technology, 2026)
The main purpose of this paper is to create a suitable maple code to generate an extremal topol ogy and to compute and list all extremal topologies over a finite set of size less than or equal to 5 points and calculate their number and the number of open sets in a generated extremal topol ogy. The Codes were developed to check if these numbers are identical to the obtained formulas. Moreover, maple procedures have been created to compute the infra-topological spaces and their number over a finite set. Computations are carried out by using Maple 2022.